Medical Record and Imaging Evaluation To Identify Arterial Tortuosity Phenotype in Populations At Risk For Intracranial Aneurysms - Diedrich, Karl T. (American Medical Informatics Association, 2011)
High arterial tortuosity may signify early arterial pathology which may precede development of intracranial aneurysms. We measured arterial tortuosity of intracranial vessels and reviewed the medical records of three groups of patients: with intracranial aneurysms, without aneurysms but at increased clinical risk, and controls without aneurysms or associated risk factors. There was significant but inconsistent evidence of increased arterial tortuosity in aneurysm cases and high-risk cases across different arteries. Medical records review identified that a subset of aneurysm cases carried a diagnosis of Loeys-Dietz syndrome that is often misdiagnosed as Marfan syndrome. We found increased arterial tortuosity in the Loeys-Dietz syndrome cases. A combination of medical record screening for Marfan syndrome or Loeys-Dietz symptoms such as aneurysms and evaluation of arterial tortuosity by a curve of scores from medical images may identify previously undiagnosed cases of Loeys-Dietz syndrome.